Carbon nanofibers from plastic solid waste - Lopes, Jéssica Paula Marim (2021)
Production of plastics reached 360 million tonnes in 2018, the EU production corresponding to 62 million tonnes (i.e. 17%), from which only 9.2 million tonnes were collected for recycling. Low- and high-density polyethylene (PE) and polypropylene (PP), commonly used for packaging purposes, represent 40% of EU production [1]. In 2018, landfilling of plastic solid waste still represented 18.5% of the collected material [1], so there is still a great fraction of plastic waste being sent to landfill, representing a strong concern, as this plastic waste does not easily decompose. On the other hand, plastic polymers are mostly composed by carbon, as both PE and PP have a carbon content of 85.6% [2]. In this context, those plastics containing PE or PP represent a good source to produce carbon-based materials. In this work, low-density PE was used as precursor for the synthesis of carbon nanofibers (CNFs) by Chemical Vapour Deposition (CVD) (800 °C, 1 h, under N2 flow), with the aim to evaluate the influence of different CVD catalysts based on Fe, Ni and Al, synthesized using coprecipitation or wet impregnation methods, on the valorisation of PE-containing plastic waste. Fig 1 displays the scanning electron micrographs (SEM) of the carbonaceous materials obtained using two different catalysts. As can be observed, filamentous carbons were obtained in both cases, attributed to the growth of CNFs. The CNFs were obtained with similar yields of carbonaceous material (37.6% with Ni+Fe@Al2O3-coprecipitation and 36.2% with Ni+Fe@Al2O3-wet impregnation). Catalyst Ni+Fe@Al2O3-coprecipitation (Fig 1(a)) led to the formation of entangled CNFs, with high density and diameters in the range 12 – 28 nm, with the catalysts metals visible at the tip of the fiber (brighter spots on the SEM image). On the other hand, the catalyst Ni+Fe@Al2O3- wet impregnation (Fig 1(b)) resulted in the growth of CNFs with higher apparent diameters, which indicates that the catalyst obtained via coprecipitation is more suitable for growing carbon nanostructures.